2004
DOI: 10.1111/j.1365-2524.2004.00467.x
|View full text |Cite
|
Sign up to set email alerts
|

Carer satisfaction with end-of-life care in Powys, Wales: a cross-sectional survey

Abstract: A cross-sectional postal survey of bereaved carers was conducted in order to examine levels of satisfaction with services provided for people in their last year of life in the rural county of Powys, Wales, UK. A self-complete questionnaire, using a modified version of the Views of Informal Carers - Evaluation of Services instrument was sent to all bereaved carers of all those people dying of cancer in Powys between 1 April 1999 and 30 June 2001. Eight hundred and five (out of a possible of 815 people) were con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 17 publications
2
34
0
Order By: Relevance
“…Only a very limited number of GPCFs presented work to external audiences out of county or within the UK during the project. Continued collaboration between GPCFs and the project evaluation team with regard to the dissemination of findings [12,15,16,11] was one way in which this issue was addressed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only a very limited number of GPCFs presented work to external audiences out of county or within the UK during the project. Continued collaboration between GPCFs and the project evaluation team with regard to the dissemination of findings [12,15,16,11] was one way in which this issue was addressed.…”
Section: Discussionmentioning
confidence: 99%
“…In this paper, we present findings relating to the first four evaluation questions. The findings relating to the views of bereaved carers are presented elsewhere [12].…”
Section: Context Materials and Methodsmentioning
confidence: 99%
“…For ethical reasons, participants were not recruited within six months of bereavement 56 . It was, however, desirable that the bereavement was not too distant and so the maximum time from bereavement was two years.…”
Section: Methodsmentioning
confidence: 99%
“…Bereaved family caregivers are at high risk for many distressing symptoms related to complex variables, such as age and gender (Brazil, Bedard, & Willison, 2002), social support (Brazil et al, 2003), available resources (Ingleton et al, 2004), and the experience of caregiving (Kris et al, 2006). A difficult caregiving trajectory was associated with poorer recovery in bereavement (Brazil et al, 2003;Gilbar & Ben-Zur, 2002;Kris et al).…”
Section: Figure 1 Suggestions For Research With Bereaved Family Carementioning
confidence: 99%
“…In a survey of 29,292 bereaved family members who had received palliative services through the NHPCO, 18% noted a need for an improvement in the support they were offered, including an increased need for communication with families and overall coordination of care (Connor, Teno, Spence, & Smith, 2005). A survey conducted in the United Kingdom with 407 bereaved family caregivers found that only 20% had the opportunity to talk to someone from health and social services after the death of their loved ones (Ingleton et al, 2004). Organizational case studies of five English hospice bereavement services in the United Kingdom revealed that all offered information, follow-up phone calls, or letters, but none used a formal risk assessment to identify who might benefit from formal bereavement support (Reid et al, 2006).…”
Section: Process: the Delivery Of Carementioning
confidence: 99%